Restorative Justice and Agrarian Reform Conflict Resolution - Alan, Muhammad Fikri (BHUMI: Jurnal Agraria dan Pertanahan, 2024)
Abstract: Various structural agrarian conflicts remain unresolved after the government's implementation of agrarian reform. Differences in interpretation of agrarian reform trigger the conflict. The government's interpretation is different from the community's interpretation, which considers agrarian reform to be a systematic effort to provide the community with access to land. This article employs an empirical legal research method, combining a sociological perspective and a case study approach. This article contains several important findings, one of which is that asset legalization is not an agrarian reform. Asset legalization fails to address the issue of land ownership inequality. The government's implementation of land redistribution fails to address the issue of land ownership inequality. The government's version of land redistribution not only fails to resolve the issue of land ownership inequality, but also seizes land from marginalized communities. The same goes for social forestry. Social forestry leaves behind unresolved agrarian and environmental conflicts. Differences in interpreting agrarian reform actually cause all these problems. Therefore, we can use restorative justice as an alternative to solving the problem. As a problem-solving model involving victims and suspects, this resolution model seeks peace between the two parties. The hope is that there will be no more bloody agrarian conflicts, especially related to agrarian reform in Indonesia. Keywords: Agrarian Reform, Agrarian Conflict, Restorative Justice